Chromosome Identification and Cytogenetic Map Construction of Zhikong Scallop (Chlamys farreri) Based on Fluorescence in situ Hybridization - Hu, Liping; Jiang, Liming; Xing, Qiang; Yang, Zujing; Zhao, Qiang; Wang, Liyong; Huang, Xiaoting; Bao, Zhenmin (Frontiers in Marine Science, 2021)
Zhikong scallop (Chlamys farreri) is a bivalve species with broad economic and biological value, and an essential species of aquaculture in North China. Recently, efforts have been made to improve knowledge of genome, genetics and cytogenetics, which is devoted to developing molecular breeding project for scallop. In this study, we constructed a cytogenetic map and identified all chromosomes of C. farreri using fluorescence in situ hybridization (FISH). A total of 100 BAC clones and 27 fosmid clones, including 58 microsatellite marker-anchored BAC clones, 4 genes-anchored BAC clones, 38 random BAC clones, 22 repetitive sequences-anchored fosmid clones and 5 gene-anchored fosmid clones, were tested as probes, and 69 of them produced specific and stable signal on one pair of chromosomes. Then, multiple co-hybridizations were conducted to distinguish all the submetacentric and subtelocentric chromosomes with similar morphology by above chromosome-specific markers. On this basis, a cytogenetic map of C. farreri containing 69 clones was constructed by co-hybridization and karyotype analysis. The markers covered all 19 pairs of chromosomes and the average number of markers on each chromosome was 3.6. The cytogenetic map provide a platform for genetic and genomic analysis of C. farreri, which facilitate molecular breeding project of C. farreri and promote comparative studies of chromosome evolution in scallops and even bivalves.